PENGOLAHAN ARSIP PETA TOPOGRAFI TNI ANGKATAN DARAT DI ARSIP NASIONAL REPUBLIK INDONESIA - , ISTRI LINA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report wrote to know and increase perception about the processing of cartographic archive especially topographic maps archive of TNI Angkatan Darat in National Archive of the Republic Indonesia. The working through of this report is begun from cartographic archive definition and topographic maps which is aimed to explain about the relevance between topographic maps with cartographic archive. The next is about the processing of topographic maps TNI Angkatan Darat procedure from archive identification, technical plan compilation, resource and reference investigation, temporary sketch compilation, reconstruction, description, definitive sketch compilation, manuver, list compilation, valuation and research, completing and legalizing. The next part explains about the format and technical in writing the list of topographic maps archive of TNI Angkatan Darat. The last is storage archive. In the processing of writing this paper use three methods to collect data. The first method is library study is useful to get book source, internet, and work regulation as reference and comparator between theory and practice. Second method is interview. Interview is used to get information from resource person who is competent in the processing of cartographic archive. The last method is participation observation. This method is done to get data for supporting this paper by observing the archive processing activity, and the writer is involved in field by following the processing of topography map archive in TNI Angkatan Darat. The conclusion of this report is the processing of topographic maps archive activity in TNI Angkatan Darat is necessary to produce archive list which is usefull as return found help facility for user who will access topographic map TNI Angkatan Darat that was transferred to National Archives of the Republic of Indonesia. It is also necessary to do storage archive in order to keep the information content security and its physic.